Commodification and authenticity: a paradoxical paradigm of older and younger generations on the preservation of mask art in Bobung Yogyakarta - Subiyantoro, Slamet; Wijaya, Yasin Surya; Kristiani, Kristiani; Maryono, Dwi (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2024)
This study aims to examine the paradigms of the younger and older generations regarding the commodification process of mask art in Bobung, Yogyakarta. The research was conducted through a descriptive qualitative approach with a multiple case study design. Data sources included informants, locations, events, and documents/archives collected through in-depth interviews, participatory observation, and content analysis. Data validity was tested using triangulation techniques and informant reviews. Interactive data analysis techniques were employed, involving data reduction, data display, and verification stages. The study findings indicate that the older and younger generations have different perspectives on the preservation and inheritance of mask art in Bobung, Yogyakarta. The older generation believes that the effective preservation of mask art should not alter the cultural order inherited from ancestors over generations. The younger generation, on the other hand, views successful preservation of mask art as needing to adapt to the developments and demands of the times, thus requiring a commodification process. The opposing paradigms, both in practice and theory, can serve as references and foundations for society, academics, practitioners, and the government on how to preserve cultural arts in an ideal and sustainable manner.